Development of Temperature-Responsive Semi-IPN Hydrogels from PVA-PNVC-PAm for Controlled Release of Anti-Cancer Agent. Issue 2 (2nd April 2016) - Sivagangi Reddy, N.; Krishna Rao, K. S. V.; Eswaramma, S.; Madhusudana Rao, K.
ABSTRACT: A series of semi-interpenetrating polymeric network (semi-IPN) hydrogels were synthesized using poly(vinyl alcohol) (PVA), monomers N-vinylcaprolactam (NVC) acrylamide (Am), and cross-linker bis[2-methacryloyloxy] ethyl phosphate (BMEP). The hydrogels were synthesized by using free-radical polymerization using ammonium persulphate (APS) as an initiator at 60°C. The hydrogels were characterized by various techniques such as Fourier transform infrared (FTIR), differential scanning calorimetry (DSC), X-ray diffraction (XRD), and scanning electron microscopy (SEM) to confirm the formation, crystallinity, and morphological behavior. The swelling behavior at various temperatures and pH conditions showed that the semi-IPN hydrogels were good candidates for temperature-responsive nature. 5-Flurouracil (FU), a model anticancer drug, was successfully encapsulated and the encapsulation efficiency was found in range of 50–74% for different hydrogels. Further, in-vitro release studies were performed to investigate the release mechanism. The cumulative release studies showed that the developed hydrogels are potentially efficient for the gastrointestinal drug delivery of FU.